On the identity of Myopilumnus andamanicus Deb, 1989 (Crustacea: Decapoda: Brachyura: Pilumnidae) from India - Trivedi, Jigneshkumar; Patel, Krupal; Mitra, Santanu; Ng, Peter K. L. (Zootaxa, 2022)
The identity of the poorly known pilumnid crab Myopilumnus andamanicus Deb, 1989 originally described from Neil Island, South Andaman Islands, India, is clarified. A re-examination of the holotype female shows that Deb’s taxon is actually a species of Lophoplax Tesch, 1918. Myopilumnus is synonymized with Lophoplax. Lophoplax andamanica n. comb. is redescribed and compared with congeners. This is the first record of Lophoplax from the Indian Ocean.